ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERATAAN LABA STUDI EMPIRIS DI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2008-2012 - Kelerek, Kelerek; Astohar, Astohar (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
This study aims to examine variable-variable firm size, profitability, financial leverage, managerial ownership and devident payout ratio to find companies that perform income smoothing practices and that not doing income smoothing practices listed in the Indonesia Stock Exchange (IDX) of the year 2008 - 2012.This study uses a quantitative approach, where the data used for the study are the financial statements of the years 2008-2012. The samples are 265 companies for 5 years in companies listed on the Indonesia Stock Exchange and were selected using purposive sampling method. Subsequently the samples were classified into groups grader profit and not income smoothing using Eckel. Analysis of the data obtained performed using logistic regression analysis.The test results of five independent variables using logistic regression showed that company size and financial leverage effect on income smoothing practices while to profitability, managerial ownership , and devident payout ratio has no effect on income smoothing practices